Does Social Health Insurance Reduce Financial Burden? Panel Data Evidence from India. (February 2018) - Azam, Mehtabul
Highlights: We examine the impact of Rashtriya Swasthya Bima Yojana (RSBY) from India. RSBY provides cashless health services to the beneficiary households. Average treatment impact on treated (ATT) is estimated. A longitudinal data is used to implement difference-in-differences with matching. We find no evidence that RSBY reduced OOP expenditure in both rural and urban areas. Summary: Indian government launched the Rashtriya Swasthya Bima Yojana (RSBY), a national health insurance scheme, in 2008 that provides cashless health services to poor households in India. We evaluate the impact of RSBY on RSBY beneficiary households' (average treatment impact on treated, ATT) utilization of health services, per capita out-of-pocket (OOP) expenditure, and per patient OOP expenditure on major morbidities. To address the issue of non-randomness in enrollment into the scheme, we exploit the longitudinal aspect of a large nationally representative household survey data to implement difference-in-differences with matching. We find that RSBY beneficiary households are more likely to report and receive treatment for long-term morbidity in rural areas; however, the differences in reporting and treatment of long-term morbidity is not statistically significant in urban areas. We do not find strong evidence that the RSBY reduced per person OOP expenditure for RSBY beneficiary households in both rural and urban areas. Conditional on having received medical treatment, we find that RSBY beneficiary patient spend less on medicine in rural areas but no statistically significant impact in urban areas. We also conduct a placebo experiment to support the parallel trend assumption of DID.